Study on a solar heat driven dual-mode adsorption chiller - Habib, K. (Elsevier Ltd, 2013)
Environmental concerns and the rising energy cost necessitate looking for renewable energy driven environmentally benign adsorption cooling systems. Solar powered adsorption chillers with non-concentrating flat plate or evacuated tube collectors face the problem of not getting adequate driving source temperature during some months of the year. Multi-staging of the adsorption cycle is then needed to exploit the low driving source temperature. A simulation study of a solar thermal driven dual-mode, four-bed silica gel-water adsorption chiller is undertaken in this work. The solar thermal collector data of Durgapur (23.48°N, 87.32°E), India has been used as the heat source for the dual-mode chiller. For a driving source temperature above 60°C, the chiller works as a single stage four-bed adsorption chiller; while the chiller functions as a two stage adsorption chiller when the driving source temperature falls below 60°C. With a cooling water temperature of 30°C, this two stage chiller has been found to produce cooling effect with a driving source temperature as low as 40°C. Results indicate that the dual-mode chiller is capable of providing cooling throughout the year under the climatic condition of Durgapur, India. © 2013 Elsevier Ltd.